An international review of the main cost-effectiveness drivers of virtual colonography versus conventional colonoscopy for colorectal cancer screening: is the tide changing due to adherence? - Kriza, Christine; Emmert, Martin; Wahlster, Philip; Niederländer, Charlotte; Kolominsky-Rabas, Peter (European Journal of Radiology, 2013)
OBJECTIVES The majority of recent cost-effectiveness reviews concluded that computerised tomographic colonography (CTC) is not a cost-effective colorectal cancer (CRC) screening strategy yet. The objective of this review is to examine cost-effectiveness of CTC versus optical colonoscopy (COL) for CRC screening and identify the main drivers influencing cost-effectiveness due to the emergence of new research. METHODS A systematic review was conducted for cost-effectiveness studies comparing CTC and COL as a screening tool and providing outcomes in life-years saved, published between January 2006 and November 2012. RESULTS Nine studies were included in the review. There was considerable heterogeneity in modelling complexity and methodology. Different model assumptions and inputs had large effects on resulting cost-effectiveness of CTC and COL. CTC was found to be dominant or cost-effective in three studies, assuming the most favourable scenario. COL was found to be not cost effective in one study. CONCLUSIONS CTC has the potential to be a cost-effective CRC screening strategy when compared to COL. The most important assumptions that influenced the cost-effectiveness of CTC and COL were related to CTC threshold-based reporting of polyps, CTC cost, CTC sensitivity for large polyps, natural history of adenoma transition to cancer, AAA parameters and importantly, adherence. There is a strong need for a differential consideration of patient adherence and compliance to CTC and COL. Recent research shows that laxative-free CTC screening has the potential to become a good alternative screening method for CRC as it can improve patient uptake of screening.

Balancing costs and benefits at different stages of medical innovation: a systematic review of Multi-criteria decision analysis (MCDA) - Wahlster, Philip; Goetghebeur, Mireille; Kriza, Christine; Niederländer, Charlotte; Kolominsky-Rabas, Peter (BMC Health Services Research, 2015)
BACKGROUND: The diffusion of health technologies from translational research to reimbursement depends on several factors included the results of health economic analysis. Recent research identified several flaws in health economic concepts. Additionally, the heterogeneous viewpoints of participating stakeholders are rarely systematically addressed in current decision-making. Multi-criteria Decision Analysis (MCDA) provides an opportunity to tackle these issues. The objective of this study was to review applications of MCDA methods in decisions addressing the trade-off between costs and benefits. METHODS: Using basic steps of the PRISMA guidelines, a systematic review of the healthcare literature was performed to identify original research articles from January 1990 to April 2014. Medline, PubMed, Springer Link and specific journals were searched. Using predefined categories, bibliographic records were systematically extracted regarding the type of policy applications, MCDA methodology, criteria used and their definitions. RESULTS: 22 studies were included in the analysis. 15 studies (68 %) used direct MCDA approaches and seven studies (32 %) used preference elicitation approaches. Four studies (19 %) focused on technologies in the early innovation process. The majority (18 studies - 81 %) examined reimbursement decisions. Decision criteria used in studies were obtained from the literature research and context-specific studies, expert opinions, and group discussions. The number of criteria ranged between three up to 15. The most frequently used criteria were health outcomes (73 %), disease impact (59 %), and implementation of the intervention (40 %). Economic criteria included cost-effectiveness criteria (14 studies, 64 %), and total costs/budget impact of an intervention (eight studies, 36 %). The process of including economic aspects is very different among studies. Some studies directly compare costs with other criteria while some include economic consideration in a second step. CONCLUSIONS: In early innovation processes, MCDA can provide information about stakeholder preferences as well as evidence needs in further development. However, only a minority of these studies include economic features due to the limited evidence. The most important economic criterion cost-effectiveness should not be included from a technical perspective as it is already a composite of costs and benefit. There is a significant lack of consensus in methodology employed by the various studies which highlights the need for guidance on application of MCDA at specific phases of an innovation.
EVALuna2:35798

Cost of illness in colorectal cancer: an international review. - Kriza, Christine; Emmert, Martin; Wahlster, Philip; Niederländer, Charlotte; Kolominsky-Rabas, Peter (PharmacoEconomics, 2013)
OBJECTIVES Given the current-and increasing-pressure to limit expenditure on health care provision in many countries, a better understanding of the cost burden of colorectal cancer is needed. Cost-of-illness studies and reviews thereof can be a useful tool for analysing and critically evaluating the cost-related development of colorectal cancer, and they highlight important cost drivers. METHODS A systematic review was conducted from 2002 to 2012 to identify cost-of-illness studies related to colorectal cancer, searching the Medline, PubMed, Science Direct, Cochrane Library and the York CRD databases. RESULTS Among the 10 studies (from France, the US, Ireland and Taiwan) included in the review, 6 studies reported prevalence-based estimates and 4 studies focussed on incidence-based data. In the studies included in the review, long-term costs for colorectal cancer of up to 50,175 per patient (2008 values) were estimated. Most of the studies in the review showed that the initial and terminal phases of colorectal cancer care are the most expensive, with continuing treatment being the least costly phase. One study also highlighted that stage I CRC disease was the least costly and stage III the most costly of all 4 stages, due to the high cost impact of biological agents. CONCLUSIONS This review has highlighted a trend for rising costs associated with CRC, which is linked to the increasing use of targeted biological therapies. COI studies in colorectal cancer can identify specific components and areas of care that are especially costly, thereby focussing attention on more cost-effective approaches, which is especially relevant to the increased use of biological agents in the field of personalised medicine. COI studies are an important tool for further health economic evaluations of personalised medicine.

Early technology foresight for the development of biomarkers for prostate cancer screening: Prospective Health Technology Assessment (ProHTA) - Niederländer, Charlotte; Kriza, Christine; Wahlster, Philip; Djanatliev, Anatoli; Kolominsky-Rabas, Peter (The European Cancer Congress 2013, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD7.earlyt_9

Gesundheitsökonomische Evaluierung eines hypothetischen Biomarkers in einem Prostata-Screening-Szenario in Deutschland unter Anwendung eines hybriden Simulationsmodells - Meier, Florian; Niederländer, Charlotte; Djanatliev, Anatoli; Gantner-Bär, Marion; Sedlmayr, Martin; Höllthaler, Josef; Voigt, Wieland; Schöffski, Oliver; Kolominsky-Rabas, Peter; German, Reinhard; Emmert, Martin (Tagungsband der 6. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.gesund

Health Economic Evaluation of a Contemplementary Biomarker for Hypothetical Prostate Cancer Screening in Germany - Meier, Florian; Niederländer, Charlotte; Djanatliev, Anatoli; Gantner-Bär, Marion; Höllthaler, Josef; Voigt, Wieland; Schöffski, Oliver; Kolominsky-Rabas, Peter; Emmert, Martin (Value in Health, 2013)
Prostate cancer (PCA) is the most common cancer in men worldwide. However, there is disagreement about the benefits of existing screening programs. This is mainly due to low specificity of currently utilized biomarkers. This can lead to both inappropriate medical treatment and increasing costs of care. For the future, many biotechnological developments are promising, but not all will be affordable for routine screening. The question is how much a complementary biomarker to prostate-specific antigen (PSA)-test may cost which would be applied to avoid false-positive result
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD7.health

Quality criteria for medical device registries: best practice approaches for improving patient safety - a systematic review of international experiences - Niederländer, Charlotte; Kriza, Christine; Kolominsky-Rabas, Peter (Expert Review of Medical Devices, 2017)
INTRODUCTION: As the benefit of medical device registries (MDRs) depends on their content and quality, it is important to ensure that MDRs have a robust and adequate structure to fulfill their objectives. However, no requirements are specified for the design and content of MDRs. The aim of this work is to analyze different MDRs in the field of implants and to give best practice recommendations for quality criteria regarding their design and development. Areas covered: A systematic literature search performed in databases (Medline, Cochrane Library, Scopus, Embase, CRD York), selected journals and websites identified 66 articles describing either a general MDR structure or the development process of specific registries. Extracted information about MDRs served as the basis for recommendations: MDRs should deliver a minimal data set and report information about the geographical area, data collection, numbers of patients enrolled, registry staff, and security and confidentiality of data. Expert commentary: Well-structured registries are a cornerstone of the regulatory process of medical devices and a major tool for decision makers. A future goal is to establish agreed minimal data sets for different devices - overcoming national borders. By establishing clear guidelines, the outcomes as well as registry comparability can be fundamentally improved.
EVALuna2:33842